1969
DOI: 10.1071/sr9690029
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the increase of cobalt in plants following the addition of a cobalt fertilizer

Abstract: The effect of applied cobalt on the cobalt content of pasture plants has been studied in pot, field, and laboratory experiments. The generally poor agreement between pot and field experiments may be partly due to the noted variation of cobalt status of pasture with season and the influence of waterlogging. Cobalt treatments were effective for at least 2 yr on the humus podzol soils, but there was only a residual effect for 1 yr on other soils. Alteration of the soil pH did not prove a satisfactory means of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Given the general low and narrow range of Co concentrations found in most soils, the first two groups are probably indistinguishable in field conditions. In fact, plant Co concentrations are typically <10 mg/kg and, more often than not, <1 mg/kg (Adams and Honeysett 1964;Adams et al 1969;Gille and Graham 1971;Gupta 1993;Klessa et al 1989;Li et al 2004;McLaren et al 1987;McLaren and Williams 1981;Nicolls and Honeysett 1964;Paterson et al 1991;Price et al 1955;Rosbrook et al 1992;Sherrell et al 1990). For comparative purposes, the threshold deficiency concentration of Co in pastures for sheep and cattle grazing has been identified as 0.05-0.1 mg/kg (Gupta 1993;Klessa et al 1989;Sherrell 1990b;Sherrell et al 1990).…”
Section: Introductionmentioning
confidence: 94%
“…Given the general low and narrow range of Co concentrations found in most soils, the first two groups are probably indistinguishable in field conditions. In fact, plant Co concentrations are typically <10 mg/kg and, more often than not, <1 mg/kg (Adams and Honeysett 1964;Adams et al 1969;Gille and Graham 1971;Gupta 1993;Klessa et al 1989;Li et al 2004;McLaren et al 1987;McLaren and Williams 1981;Nicolls and Honeysett 1964;Paterson et al 1991;Price et al 1955;Rosbrook et al 1992;Sherrell et al 1990). For comparative purposes, the threshold deficiency concentration of Co in pastures for sheep and cattle grazing has been identified as 0.05-0.1 mg/kg (Gupta 1993;Klessa et al 1989;Sherrell 1990b;Sherrell et al 1990).…”
Section: Introductionmentioning
confidence: 94%
“…The cation-exchange preference of birnessite for heavy metals makes it important from a pollution-abatement point of view and in controlling the availability of certain trace elements, some of which are essential to plants and animals (e.g., Co and Cu). Adams et al (1969) showed that the availability of cobalt to plants is controlled to a large extent by the amount of manganese in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to relate soiI micronutrient adsorption characteristics to plant uptake of micronutrients added to the soil have been generally more successful than the studies with native soiI micronutrients. For example Adams et al (1969) and McLaren et al (1987) have both shown that, at least in the short term, uptake of fertilizer Co can be related to the gradients of soil Co adsorption isotherms (Figure 9.31 and 9.32).…”
Section: Adsorption and Desorption In Relation To Micro-nutrient Uptamentioning
confidence: 94%